Tenacious solidarity : Biblical provocations on race, religion, climate, and the economy - Brueggemann, Walter
Tenacious Solidarity features essays and new writings from 2014 to 2018. The author brings the ""transformative potential"" of the biblical texts to bear on critical contemporary contexts, including but not limited to economic disparities, racial injustice and white supremacy, climate and care for creation, the power of memory and mentoring, and his insights on best practices for interpreting the Hebrew Bible texts.